Analisis Penerimaan Perpustakaan Itenas Pada Online Public Access Catalog Menggunakan Metode Technology Acceptance Model - Rai Dzikri Nugraha, dkk, Muhammad (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Using the Technology Acceptance Model (TAM) approach, this study attempts to investigate and evaluate user acceptance of a library information system based on the Online Public Access Catalog (OPAC). In addition to evaluating theories about how these factors affect user attitudes, intentions, and actual usage, the main goal is to assess the elements that affect user perceptions, namely perceived usefulness and ease of use. Library patrons were given questionnaires to complete in order to gather data. The results show that perceived usefulness, which in turn influences user attitudes and intentions to utilize OPAC, is highly influenced by perceived simplicity of use. Thus, this study evaluates the influence among variables based on the TAM framework in addition to providing insights into important criteria for improving the adoption of library information systems.